2020
DOI: 10.1371/journal.pone.0228951
|View full text |Cite
|
Sign up to set email alerts
|

Segregation distortion: Utilizing simulated genotyping data to evaluate statistical methods

Abstract: Segregation distortion is the phenomenon in which genotypes deviate from expected Mendelian ratios in the progeny of a cross between two varieties or species. There is not currently a widely used consensus for the appropriate statistical test, or more specifically the multiple testing correction procedure, used to detect segregation distortion for high-density single-nucleotide polymorphism (SNP) data. Here we examine the efficacy of various multiple testing procedures, including chi-square test with no correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The current VRS-F 2 GBS-rhAmpSeq integrated map includes markers that deviate from Mendelian segregation 1:2:1 ratio for chromosome 5, 7, 11, and 15. The addition of some of the distorted markers did not show any effect on marker order or recombination percentage, suggesting that marker segregation distortion is natural in these chromosomal regions for this F 2 grapevine population [ 39 , 40 ]. The inclusion of these markers increased marker density and filled long gaps in the genetic map on chromosomes 5, 7, 11, and 15.…”
Section: Discussionmentioning
confidence: 99%
“…The current VRS-F 2 GBS-rhAmpSeq integrated map includes markers that deviate from Mendelian segregation 1:2:1 ratio for chromosome 5, 7, 11, and 15. The addition of some of the distorted markers did not show any effect on marker order or recombination percentage, suggesting that marker segregation distortion is natural in these chromosomal regions for this F 2 grapevine population [ 39 , 40 ]. The inclusion of these markers increased marker density and filled long gaps in the genetic map on chromosomes 5, 7, 11, and 15.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2008) 26 reported that QTL mapping could benefit from using all available (‘Mendelian’ + ‘distorted’) marker resources. Recently, Coulton et al 27 reported that markers that showed extreme segregation distortion affected the estimation of recombination between marker pairs and hence should be discarded. In this study, Chi-square goodness of test was used to measure deviation from a 1:1 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…For the construction of consensus map, 1 492 polymorphic markers were applied to generate the genetic map, after removing the duplicated markers. The details of the markers and their sequences are shown in Supplementary Table S1 Linkage Map Construction and Determination of the Segregation Distortion of Molecular Markers Markers with less than 5% missing data were used in the mapping of the linkage groups in the three maps (Coulton et al 2020). The Joinmap 4.0 mapping tool was applied with a recombination frequency of 0.40, and a LOD score of 3.0, any LOD above 2.5 is known to be above the noise level (Faleiro et al 2003).…”
Section: Molecular Markers Genotypingmentioning
confidence: 99%